Safeguarding open spaces in the Alpine region - Blanka Bartol; Jernej Červek; Benoît Fanjeau; Lenča Humerca Šolar; Hubert Job; Andreas Klee; Peter Laner; Florian Lintzmeyer; Constantin Meyer; Živa Novljan; Andre Omizzolo; Luisa Pedrazzini; et al. (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2022)
A group of members of the AlpPlan Alpine spatial planning network elaborated this position paper. It contains assessments and recommendations related to key spatial challenges of transnational relevance in the Alpine region. It generally refers to the entire Alpine macroregion (EUSALP perimeter). However, some issues are particularly relevant to the core Alpine area, defined by the Alpine Convention perimeter. The paper is addressed to spatial planners, decision makers and all stakeholders involved in sustainable territorial development of the Alpine region. The specific circumstances, spatial planning systems and instruments in the various Alpine states and regions differ to some extent. Therefore, the recommendations should always be interpreted in the respective national, regional or local context.
urn:nbn:de:0156-01339
Keywords: 710